Meningkatkan Brand Image dengan Menggunakan Website Berbasis UI/UX - Fauzi, Ahmad; Rokhim, Muh. Alfin (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
Meet Indonesia is a provider of high-quality goalkeeper gloves that currently markets its products through social media and e-commerce. However, the owner wants to improve the brand image through a more flexible independent platform to face intense industrial competition.  This research aims to design a UI/UX-based sales website using CMS Wordpress to enhance Meet Indonesia's brand image and systematically evaluate its quality. The type of research used is action research involving 15 respondents as samples (2 computer experts, 2 marketing experts, 1 owner, and 10 consumers). Data collection techniques were carried out through observation, interviews, documentation, and Likert scale questionnaires. Data analysis was performed using the WebQual Index method to measure service quality and the HEART Framework to measure user experience. The results of the analysis using WebQual showed a WebQual Index (WQI) value of 91.67%, which falls into the "Very Good" category, while the evaluation using the HEART Framework produced a total overall score of 93.54%, reflecting a very high quality of user experience in the dimensions of Happiness, Engagement, Adoption, Retention, and Task Success. The developed website is proven to be able to provide a significant contribution in improving Meet Indonesia's brand image by presenting a positive experience for users both emotionally and functionally, thereby increasing user trust in the brand and encouraging consumer loyalty